Environmental Impacts of Cotton Spinning Mills: A Review of Mitigation Strategies - Dr. Qamar Tusief Awan; Ibtisam Ahmad; Muhammad Talha; Menahil Israr; Hammad Hassan Shah; Ahmad Ilyas; Muhammad Abdullah Zaid; Fatima Waqar; Nabeeha Batool; Muhammad Zain; Abdullah Khan; Aleena Aftab (`, 2025)
The cotton spinning industry is an essential part of the textile value chain and plays a significant role in the economy of cotton producing countries. However, cotton spinning mills are associated with various environmental challenges, mainly due to high energy consumption, cotton dust emissions, solid waste generation, noise pollution, and indirect impacts related to water use. In recent years, increasing environmental regulations, rising energy costs, and sustainability demands from international buyers have highlighted the need for environmentally responsible spinning practices. This review examines recent literature on the environmental impacts of cotton spinning mills and discusses mitigation strategies reported by researchers and industry studies. Key areas of focus include energy efficiency improvement, renewable energy use, air pollution control, waste minimization and recycling, and the application of environmental management systems. The paper also discusses the current environmental scenario of cotton spinning mills in Pakistan, identifying major challenges as well as opportunities for improvement. Overall, the review shows that practical technological and management-based measures can reduce environmental impacts while maintaining production efficiency and it highlights the need for further research and policy support to promote sustainable cotton spinning operations. Keywords: Cotton Spinning; Environmental Impacts; Sustainability; Energy Efficiency; Waste Recycling; Pakistan Textile Industry